Antimicrobial Susceptibility Patterns in Neisseria gonorrhoeae Isolated from South African Pregnant Women. (28th March 2021) - Oree, Glynis; Naicker, Meleshni; Maise, Hopolang Clifford; Tinarwo, Partson; Abbai, Nathlee Samantha
Abstract : Background . Neisseria gonorrhoeae, a sexually transmitted infection, is associated with adverse pregnancy and neonatal outcomes. Emerging resistance towards various antibiotics has been observed globally. However, there is a lack of data on antimicrobial susceptibility patterns in N. gonorrhoeae isolated from pregnant women in our setting. This study fills in this gap in the literature. Methods . The study population included pregnant women, recruited from the antenatal clinic of the King Edward VIII hospital (KEH) in Durban. Endocervical swabs were obtained from 307 women. The swab was placed in Amies Charcoal media for culture assessments. Pure isolates of N. gonorrhoeae were subjected to antimicrobial susceptibility testing using the Etest™ method. The MIC values were assessed in accordance with the European Committee on Antimicrobial Susceptibility Testing (EUCAST, 2019) breakpoints. Results . The prevalence of N. gonorrhoeae by culture was 1.9%. High MIC values to penicillin G (12-64 mg/L) indicating a resistant phenotype were observed for all isolates tested, with 50% of the isolates displaying complete resistance. Isolates with intermediate (1 mg/L) and resistance (1.9-32 mg/L) profiles to tetracycline were observed. Resistance to ciprofloxacin (1.16-3 mg/L) was also observed. Isolates displayed either dual or triple resistance to penicillin G, tetracycline, or ciprofloxacin. All isolates showed susceptibility to spectinomycin (>64 mg/L), azithromycin (1 mg/L), ceftriaxone (>0.125 mg/L), and cefixime (>0.125 mg/L). Conclusion . Despite lack of resistance to ceftriaxone and azithromycin, continuous surveillance for emerging patterns of resistance to these antibiotics is needed since they form part of the treatment guidelines.